Electrical properties of materials - Solymar, L. (Laszlo); Syms, R. R. A. (Oxford University Press, 2019)
A classic text in the field providing a readable and accessible guide for students of electrical and electronic engineering. Fundamentals of electric properties of materials are illustrated and put into context with contemporary applications in engineering. Mathematical content is kept to a minimum allowing the reader to focus on the subject. The starting point is the behaviour of the electron, which is explored both in the classical and in the quantum-mechanical context. Then comes the study of bonds, the free electron model, band structure, and the theory of semiconductors, followed by a chapter on semiconductor devices. Further chapters are concerned with the fundamentals of dielectrics, magnetic materials, lasers, optoelectronics, and superconductivity. The last chapter is on metamaterials, which has been a quite popular subject in the past decade. The book includes problems, the worked solutions are available in a separate publication: Solutions manual for electrical properties of materials. There is an appendix giving a list of Nobel Prize winners whose work was crucial for describing the electric properties of materials, and there are further appendices giving descriptions of phenomena which did not fit easily within the main text. In particular there is a quite detailed appendix that summarizes the properties of memory elements. The book is ideal for undergraduates, and is also an invaluable reference for graduate students and others wishing to explore this rapidly changing field.